2021
DOI: 10.3389/fnut.2021.644800
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Dietary Behavior Changes Due to the COVID-19 Confinement in Colombia: A National and Regional Survey Study

Abstract: The aim of this study was to evaluate the impact of coronavirus SARS-Cov2 (COVID-19) confinement measures in Colombia on the dietary behaviors of a large population sample, at national and regional levels. A survey was conducted to assess dietary behaviors during the COVID-19 confinement. The survey involved 2,745 participants, aged 18 years or older, from six regions of the country (Atlántica, Bogotá, Central, Oriental, Orinoquía and Amazonía, and Pacífica). Dietary intake of foods and foods groups in grams p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 35 publications
1
29
0
1
Order By: Relevance
“…An increase in red and processed meat consumption from 20.0% to 51.1% was reported by 14 investigations ( 4 , 22 , 31 , 33 , 35 , 38 , 43 , 45 , 61 , 62 , 77 , 95 , 96 , 113 ), whereas 17 studies pointed to a decreasing consumption from 6.7% to 24.4% ( 20 , 23 , 25 , 26 , 32 , 41 , 42 , 44 , 59 , 60 , 63 , 65 , 76 , 78 , 90 , 110 , 111 ). Olive oil was consistently found to be increased from 12.4% to 12.6% in all studies addressing this issue ( 25 , 33 , 60 , 65 , 111 ) As reported by 19 studies ( 4 , 20 , 22 , 25 , 32 , 35 , 41–44 , 60 , 63 , 67 , 76 , 77 , 86 , 110 , 111 , 113 ), fish and seafood intakes significantly decreased from 9.4% to 31.3%; conversely, only 6 studies observed an increase ( 33 , 45 , 59 , 65 , 81 , 95 ).…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…An increase in red and processed meat consumption from 20.0% to 51.1% was reported by 14 investigations ( 4 , 22 , 31 , 33 , 35 , 38 , 43 , 45 , 61 , 62 , 77 , 95 , 96 , 113 ), whereas 17 studies pointed to a decreasing consumption from 6.7% to 24.4% ( 20 , 23 , 25 , 26 , 32 , 41 , 42 , 44 , 59 , 60 , 63 , 65 , 76 , 78 , 90 , 110 , 111 ). Olive oil was consistently found to be increased from 12.4% to 12.6% in all studies addressing this issue ( 25 , 33 , 60 , 65 , 111 ) As reported by 19 studies ( 4 , 20 , 22 , 25 , 32 , 35 , 41–44 , 60 , 63 , 67 , 76 , 77 , 86 , 110 , 111 , 113 ), fish and seafood intakes significantly decreased from 9.4% to 31.3%; conversely, only 6 studies observed an increase ( 33 , 45 , 59 , 65 , 81 , 95 ).…”
Section: Resultsmentioning
confidence: 51%
“…Sharp changes were observed also for legumes, with 17 studies registering increased consumption from 10.9% to 21.9% ( 4 , 25 , 26 , 33 , 41 , 42 , 44 , 45 , 60 , 65 , 76 , 86 , 89 , 90 , 95 , 96 , 111 ); in contrast, a reduction from 9.9% to 25.9% was observed in only 4 of the included studies ( 22 , 59 , 82 , 99 ). An increase in red and processed meat consumption from 20.0% to 51.1% was reported by 14 investigations ( 4 , 22 , 31 , 33 , 35 , 38 , 43 , 45 , 61 , 62 , 77 , 95 , 96 , 113 ), whereas 17 studies pointed to a decreasing consumption from 6.7% to 24.4% ( 20 , 23 , 25 , 26 , 32 , 41 , 42 , 44 , 59 , 60 , 63 , 65 , 76 , 78 , 90 , 110 , 111 ).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…However, the nutrient values of vegetables can vary thousandfold among different varieties of the same food (23). Many studies on Covid-19 and dietary changes looked at overall changes in food purchasing patterns, consumption and lifestyle only and paid little attention to dietary diversity or even diversity within a food group (6,8,9,12,24). The "Food systems in times of COVID19" (COVID-Food systems) project aimed to identify how the observed constraints affect the food systems and dietary behaviour of populations across the globe.…”
Section: Introductionmentioning
confidence: 99%